Association Relationship between Personal Variables and Numbers of ICTs, Accessibility of ICTs, Agriculture Practices and Animal Husbandry Practices: Study in Haryana - Kumar , Rupender; Hudda, R. S.; Malik, Joginder Singh; Mehta , S. K.; Mehta, Gagan (Indian Journal of Extension Education, 2017)
The present study was carried out in four districts of Haryana state i.e., Yamunanagar, Karnal, Hisar and Fatehabad, which  were selected randomly. In total 240 respondents viz., 60 farmers from each district, 30 farmers from each block and 15  farmers from each village were selected for the present study. Correlation coefficient and regression coefficient of  personal variables were found positively significant, negative significantly and non significant with numbers of ICTs,  accessibility of ICTs, agriculture practices information and animal husbandry practices.
Keywords: ICT; Accessibility; Agriculture and Animal husbandry Practices